Solve the system of equations 3x + y = 3 and 7x + 2y = 1.
1. Solve for the variable y in the first equation:
y=3 - 3x
2. Substitute the value for y into the second equation: 7x + 2(3 - 3x) = 1
3. Solve forx:
X=

Respuesta :

Answer:

  (x, y) = (-5, 18)

Step-by-step explanation:

You have done the first two steps.

3.

  7x +2(3 -3x) = 1 . . . . . equation with y substituted

  7x +6 -6x = 1 . . . . . . . eliminate parentheses using the distributive property

  x = -5 . . . . . . . . . . . . . subtract 6 from both sides, collect terms

4.

  y = 3 -3(-5) . . . . . . . . use the substitution equation to find y

  y = 18

The solution is (x, y) = (-5, 18).

Ver imagen sqdancefan
ACCESS MORE